PENERAPAN SIX SIGMA DALAM RANCANGAN PERCOBAAN FAKTORIAL UNTUK MENENTUKAN SETTING MESIN PRODUKSI AIR MINERAL - Muhammad Nugroho Karim Amrulllah; Mustafid Mustafid; Sugito Sugito (Jurnal Gaussian, 2016)
Machine setting is one of the factors which affects the high defects of mineral water cup. The determination of the optimal machine setting is needed to reduce the defects that occur. Six Sigma DMAIC (define, measure, analyze, improve, control) method in the factorial experimental design can be used for determining the optimal machine setting. This research, which is conducted in PT Sekar Sari, found the most optimal combination of pressure and temperature setting of the machine, so that the defects generated are decreasing after optimal condition treatment. Sigma level increased by 0.89 sigma, from 2,47 sigma to 3,36 sigma and COPQ (cost of poor quality) percentage decreased by 3.64%.Keywords: Six Sigma, DMAIC, Factorial Design of Experiment, COPQ.